Therapeutic Potential of Polyphenol and Nanoparticles Mediated Delivery in Periodontal Inflammation: A Review of Current Trends and Future Perspectives - Jayusman, Putri Ayu; Nasruddin, Nurrul Shaqinah; Mahamad Apandi, Nurul Inaas; Ibrahim, Norliwati; Budin, Siti Balkis (Frontiers in Pharmacology, 2022)
Periodontitis is an oral inflammatory disease of the periodontium, which occur primarily due to microbial invasion that causes destruction of gingival connective tissue and the alveolar bone supporting the teeth. Host immune and inflammatory responses induce by specific oral pathogens and their metabolic products are responsible for the local tissue destruction. Numerous studies in the past decades have demonstrated that natural polyphenols are capable of modulating the host inflammatory responses by targeting multiple inflammatory components. Polyphenolic compounds have the ability to regulate immunity by interfering with immune cell regulation, proinflammatory cytokines’ synthesis, and gene expression. However, due to its low absorption and bioavailability, the beneficial effects of these substances are very limited and it hampers their use as a therapeutic agent. To address these limitations, targeted delivery system by nanoencapsulation techniques have been explored in recent years. Nanoencapsulation of polyphenolic compounds with different carriers is an efficient and promising approach to boost their bioavailability, increase the efficiency and reduce the degradability of natural polyphenols. In this review, we focus on the effects of different polyphenolic substances in periodontal inflammation and to explore the pharmaceutical significance of polyphenol-loaded nanoparticles in controlling periodontitis, which may be useful for further enhancement of their efficacy as therapeutic agents for periodontal disease.